Inflammation and α-Synuclein’s Prion-like Behavior in Parkinson's Disease—Is There a Link? - Lema Tomé, Carla M. (Humana Press Inc, 2012)
Parkinson’s disease patients exhibit progressive spreading of aggregated α-synuclein in the nervous system. This slow process follows a specific pattern in an inflamed tissue environment. Recent research suggests that prion-like mechanisms contribute to the propagation of α-synuclein pathology. Little is known about factors that might affect the prion-like behavior of misfolded α-synuclein. In this review, we suggest that neuroinflammation plays an important role. We discuss causes of inflammation in the olfactory bulb and gastrointestinal tract and how this may promote the initial misfolding and aggregation of α-synuclein, which might set in motion events that lead to Parkinson's disease neuropathology. We propose that neuroinflammation promotes the prion-like behavior of α-synuclein and that novel anti-inflammatory therapies targeting this mechanism could slow disease progression.